Number of Preoperative Hyperhidrosis Sites Does Not Affect the Sympathectomy Postoperative Results and Compensatory Hyperhidrosis Occurrence - Wolosker, Nelson; Leiderman, Dafne Braga Diamante; de Campos, Jose Ribas Millanez; Kauffman, Paulo; Tedde, Miguel Lia; Yazbek, Guilherme; Puech-Leão, Pedro (The Thoracic and Cardiovascular Surgeon, 2019)
Background Patients with primary hyperhidrosis present with sweating in two or more sites in nearly 85% of cases. In this study, we examined whether the number of hyperhidrosis sites is related to the surgery outcomes.Methods One hundred ninety-three hyperhidrosis patients who underwent bilateral videothoracoscopic sympathectomy after failure or dissatisfaction with clinical treatment were distributed into three groups based on the number of hyperhidrosis sites (one site, two sites, and three or more sites of hyperhidrosis). The primary endpoints in the study were as follows: quality of life prior to surgery, improvement of quality of life after surgery, clinical improvement of sweating, presence or absence of compensatory hyperhidrosis, and general satisfaction after 1 month of surgery.Results Patients with two or more hyperhidrosis sites had worse quality of life before surgery than patients with a single hyperhidrosis site. There was an improvement in the quality of life in more than 95% of the patients, clinical improvement in more than 95% of patients, severe compensatory hyperhidrosis in less than 10%, and low general satisfaction after 1 month of surgery in only 2.60% of the patients, with no differences among the three groups.Conclusions Patients with more than one preoperative hyperhidrosis site present worse quality of life prior to surgery than those with a single hyperhidrosis site, but the number of hyperhidrosis sites before surgery does not affect surgery outcomes.
Keywords: hyperhidrosis; compensatory hyperhidrosis; quality of life; sympathectomy; thoracoscopy